Meeting the challenge he Hexagon KH-9 reconnaissance satellite - Pressel, Philip (Library of flight, 2013)
This is the declassified story of the design, development, production, and operation of the Hexagon KH-9 reconnaissance satellite, which provided invaluable photographic intelligence to the U.S. government, and stands as one of the most complicated systems ever put into space.